The hidden staircase - Keene, Carolyn (New York : Grosset & Dunlap, 1959)
Strange things happen when Nancy investigates threats against her father and an old house said to be haunted.
4.9
5-8
780L
Keywords: Mystery and detective stories; Rescue work -- Fiction; Wills -- Fiction; Mystery fiction